Majaz in the Qur’an Between Acceptance and Rejection - Alfian Mubarok; Silvia Marina; Lutfiah Amaliyah; Aisya Amir; Uwoh Abdullah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
Arabic is the main medium for conveying revelation in the Qur'an, known to have a deep rhetorical structure and full of expressive nuances. One important element in its aesthetic power and expressive meaning is the existence of majaz, namely the use of figurative language that replaces the literal meaning with another meaning that is conceptually related. In the study of balaghah, majaz is seen as a linguistic instrument that allows the development of meaning without deviating from the rules of language. However, the existence of majaz in the Qur'an has become a widespread discussion and has given rise to different views among commentators. Various previous studies have examined linguistic aspects of the Qur'an, such as phonology, morphology, and syntax, and how these three elements contribute to the beauty and power of the divine message. A number of studies have highlighted how phonological elements in the recitation of the Qur'an can strengthen the emotional impact, for example by creating an impression of softness or firmness through the choice of certain sounds. There are also studies that explore the relationship between phonological form and semantic meaning in the verses of the Qur'an. However, there are still few studies that deeply and integratedly examine how phonology, morphology, and syntax interact in forming the emotional effects felt by readers and listeners of the Qur'an. This study aims to describe and analyze the phenomenon of majaz in the Qur'an between acceptance and rejection among interpreters. The novelty of this study lies in its approach that examines majaz comprehensively from various linguistic and theological perspectives.